Earthquake and the pandemic on top of old problems – work of the Croatian History Museum after the Zagreb earthquake of March 2020 and during the Covid-19 pandemic (Libellarium: journal for research in the field of information and related sciences, 2022)
Purpose. The aim of the paper is to present the work the Croatian History Museum (CHM) has done to preserve cultural heritage and the use of its digital strategy to present that work. This was applied in the CHM’s plan as the digital editorial board was formed to oversee and curate the Museum’s presence on the social media and the internet. Approach/methodology. The paper showcases the increase of online visitors and users that consume cultural heritage on online platforms through the examples of virtual exhibitions, social media posts and gathered data. The maintenance of a specifically targeted virtual identity of a museum helped in this regard, which is evident in the increase of online visitors. Data was gathered and interpreted by using Google Analytics and Instagram analytical data by the author throughout 2020, and the data suggest that digital museums have a lot of potential, in particular with modern online users. Findings. The data presented in the paper shows that the online visitors were interested in the work of the Museum and that the promotion thorough social media generated online visitors as much as a real-life exhibition. It shows the interest in digital museums and the promotion of museum work online.Research limitations. The author recognizes that the data presented in the paper is gathered only from one source as the author could not access data from other similar institutions which would have been used for comparison.Originality/value. Through empirical examples, the paper showcases how useful a virtual museum can be in raising interest in cultural heritage. This is especially important in times when people cannot attend large social gatherings. Also, the paper describes the events and the work guidelines given at times of crisis such as earthquakes, which the author witnessed himself and participated in.
Keywords: cultural heritage; digitization; history; museum; social media; virtual museum